Evidence of β-antimonene at the Sb/Bi2Se3 interface. (10th January 2018) - Flammini, R; Colonna, S; Hogan, C; Mahatha, S K; Papagno, M; Barla, A; Sheverdyaeva, P M; Moras, P; Aliev, Z S; Babanly, M B; Chulkov, E V; Carbone, C; et al.
Abstract: We report a study of the interface between antimony and the prototypical topological insulator Bi2 Se3 . Scanning tunnelling microscopy measurements show the presence of ordered domains displaying a perfect lattice match with bismuth selenide. Density functional theory calculations of the most stable atomic configurations demonstrate that the ordered domains can be attributed to stacks of β -antimonene.